1998
DOI: 10.1007/s005350050072
|View full text |Cite
|
Sign up to set email alerts
|

Increased mRNA expression of a novel prostacyclin-stimulating factor in human colon cancer

Abstract: We recently cloned a prostacyclin (PGl2)-stimulating factor (PSF), which stimulates PGl2 production by cultured vascular endothelial cells. Immunohistochemistry and Northern blot analysis demonstrated that PSF was highly expressed in colon cancer sites compared with normal colon mucosa obtained from the same patient, as well as in cultured adenocarcinoma cell lines compared with cultured normal colon mucosal cell lines. Increased levels of the PSF protein were detected in the culture media of these adenocarcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
1
12
1
Order By: Relevance
“…In the present study, we further strengthened the previous report concerning increased expression of IGFBP-rP1 in colorectal cancer. This is consistent with the report of Umeda et al (1998). Tumor samples with upregulated expression of IGFBP-rP1 in invading tumor cells showed an increased frequency of metastasis to lymph nodes and an increased depth of infiltration.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, we further strengthened the previous report concerning increased expression of IGFBP-rP1 in colorectal cancer. This is consistent with the report of Umeda et al (1998). Tumor samples with upregulated expression of IGFBP-rP1 in invading tumor cells showed an increased frequency of metastasis to lymph nodes and an increased depth of infiltration.…”
Section: Discussionsupporting
confidence: 82%
“…As there is currently no clear understanding whether late-stage angiogenesis contributes to tumor progression or tumor growth stabilization, the overall effect of IGFBP7 in tumor milieu cannot be easily generalized. Further understanding of the regulation and functions of this highly selective biomarker of tumor vessels will be important in developing appropriate therapies for GBM tumors as well as other tumors characterized by high vascular expression of IGFBP7 such as colon cancer (Umeda et al, 1998;van Beijnum et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…8,[15][16][17][18][19] For clarifying its physiological and pathological functions, it appears essential to know its fine distribution in vivo. We demonstrate here that AGM expression on blood vessels relates to clinicopathological parameters of human cancers and that AGM expression on cancer cells correlates with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…14 There are various AGM expression patterns and functions with varying tumor types: AGM is reported to have a tumor suppressor-like function in breast, prostate and cervical cancers, as well as osteosarcomas, 8,15,16 while it is associated with tumorigenesis in prostate cancer, colorectal cancer, and uterine leiomyoma. [17][18][19] Although past studies have suggested involvement of AGM in tumor growth and progression, its clinical significance and exact function remain unknown. AGM is reported to be expressed in colon cancer; however, there is no precise report on AGM in human colorectal cancer.…”
mentioning
confidence: 99%